Improvements of Centry-2 for the dialysis with bicarbonate - Ogasawara, M.; NAKAMURA, Y.; NAOI, T.; OHWADA, H.; SAKAGAWA, K.; TAKAHASHI, M. (Jinko Zoki, 1985)
We made an improved system of Centry-2, which enable easily to exchange acetate dialysate for bicarbonate one. The new system is briefly indicated below. Basic dialysate without bicarbonate (Solution A) is diluted by the ordinary system of Centry-2. (Solution A). Solution B (5% HCO-3) is infused into Solution A' between the control conductivity cell and the stabilyzer by the additional supply pump. (Solution A'+B). The control converter, which monitors the concentration of both Solution A and Solution A'+B, was newly constructed. Results of running test showed good stability of this system. The nature of Solution A'+B was of pH 7.194±0.009, PCO265.9±1.7mmHg, HCO-3 25.4±0.6mEq/L, Na 139.6±0.7mEq/L and K 2.4±0.0mEq/L. These improvements of Centry-2 are very simple and not so expensive as other bicarbonate infusers. Therefore this system is very useful for the dialysis with bicarbonate.